PEMETAAN MULTI-BENCANA PADA JALUR KERETA API LINTAS SELATAN DARI STA. WATES-STA. KUTOWINANGUN - Muhammad fauzi Fauzi (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
Wates – Kutowinangun railway geographically locates in south way near south coast directly borderingto Indie Ocean. The people know the train transportation mode as most effective mode in terms of time and cost aspects. However, this train transportation mode has weaknesses; one of these weaknesses is delay/hour of departure due to accident or area passed by the railway experienced natural disaster. Some of disasters that couldinhibit railway travel were flood and tsunami. This study aimed at identifying and mapping potentials of multipledisasters (flood and tsunami) that could affect performance of railway from Wates station to Kutowinangun stationusing GIS (Geographic Information System) with ArcGIS software. In this study, evaluation method used landscape analysis usable to find disaster vulnerability rate.